Effect of structured teaching guidelines on patient's knowledge, practice, and self-efficacy regarding colostomy care - El-Sayead Shrief, Sheren; Mokhtar Mokhtar, Islam (International Journal of Advanced Nursing Studies, 2019)
Background: nurses are primarily health professional who is engaged in the management of colostomized individuals who go through different physical and psychosocial transformations.Aim: to evaluate the effect of applying structured teaching guidelines on patient's knowledge, practice, and self-efficacy regarding colostomy care.Hypothesis: application of structured teaching guidelines will have a positive impact on patient's knowledge, practice, and self-efficacy regarding colostomy care. Design: pre-post analytic study.Setting: the study was carried out in the surgical department, and outpatient clinic at Beni-Suef University hospital and Aswan oncology Hospital.Sample: A total number of 50 adult patients, both sex, conscious, having a permanent colostomyTools: four tools were utilized in this study; Tool I: A structured interview questionnaire sheet which comprised two parts: Part I: Personal characteristics of the studied patients, Part II: Patients` knowledge about colostomy care; Tool II: Patient's Generalized Self-Efficacy Scale; Tool III: An observation checklist (pre/post /follow â€“ up assessment) and Tool IV: The structured teaching Guidelines.Results: There was a statistically significant distinction between both the study and control group regarding patient's knowledge, practice, and self-efficacy regarding colostomy care.Conclusion: Application of the structured teaching guidelines had a positive impact on patient's knowledge, practice and self-efficacy regarding colostomy care with an obvious statistically significant distinction between pre and post-intervention.Recommendations: Replication of the same study on larger probability sample at different geographical locations for data generalizability, and distribution of the booklet for patients with a colostomy to improve their outcomes.Â Â